Study of Phenomenon STT (Spin Transfer Torque) on Permalloy NiFe Material Shaped Nanowire Using Micromagnetic Simulation - Ni’mah, Khiptiatun; Rohman, Lutfi; Purwandari, Endhah (Computational And Experimental Research In Materials And Renewable Energy, 2019)
STT is a process of controlling the spin currents in spintronic. This simulation aims to know the properties of NiFe permalloy materials' properties by studying STT phenomenon-shaped nanowire that can be applied in storage devices, like MRAM. The material's magnetic properties include magnetization value, energy in the ferromagnetic system, and the speed of the domain wall movement, obtained by injecting the electric current density through a micromagnetic simulation using the NMAG program. This simulation's result is that the domain wall's position will shift faster along the nanowire when we inject current density to the nanowire. Current density injection will produce a domain wall pressure on the domain structure, resulting in a change in the material's magnetization value. The graph of magnetization relation to time (M-t), shown along with the increasing electric current density, we obtain oscillation magnetization change will increase. The larger the given diameter, the total energy generated will increase, demagnetization energy tends to be greater than the energy exchange. The greater the polarization of the material provided at the same diameter, the speed of the domain wall movement will be greater too.